Analisis Semiotika Nilai Dakwah dalam Lagu Jiwa yang Bersedih Karya Ghea Indrawari - Muhammad Rifqi Rosyaddin; Bambang Saiful Ma’arif; Nia Kurniati (UNISBA Press, 2024)
Abstract. This research focuses on the da'wah method through song media, especially through a song by Ghea Indrawari entitled